Optimalisasi peran guru madrasah terhadap penggunaan Bahasa Indonesia dalam pembelajaran: Studi pada Siswa Madrasah Ibtidaiyah Muhammadiyah Qomariah Klego - Marwanto, Marwanto (Journal of Smart Education and Learning, 2024)
This study uses a qualitative descriptive approach. Qualitative because it must conduct interviews and collect documents, after which it is described. The aim is to determine the optimization of the role of madrasah teachers in using Indonesian in learning for students of Madrasah Ibtidaiyah Muhammadiyah Qomariah Klego. The research took place at MI Muhammadiyah Qomariyah Klego. There are 17 teachers and 301 students. This study's primary data source was interviews covering the principal, vice principal for curriculum, religious teachers, assistant teachers, teachers, students, and parents. Data collection techniques used observation, documentation, and interviews covering the principal (one person), vice principal for curriculum (one person), religious teachers (two people), language teachers (four people), students (6 children), and parents (two people). The study results showed that the teachers gradually began to use Indonesian but still interspersed it with mixed or regional languages. They patiently taught and guided students until they could communicate well in Indonesian. The MI Muhammadiyah Qomariyah Klego teachers have carried out their learning tasks optimally.